CPR-Induced Life-Threatening Hemothorax in a Rescue PCI Patient: Case Report and Brief Challenges of Regional Centers - Vaikunthan Thanabalasingam; Clement Tan; Chaminda Sella Kapu; Mark Daniel Higgins; Zhihua Zhang (Reports)
Background: Cardiopulmonary resuscitation (CPR) is performed in cardiac arrests. There exist life support guidelines for individuals in performing effective CPR. CPR-related bleeding and hemothoraces are rare. Intercostal artery rupture leading up to shock and respiratory compromise in such situations is rare. Here, we present a unique case with a management dilemma while discussing challenges and guidance to regional centers. Case presentation: A 49-year-old Caucasian male experienced an out-of-hospital cardiac arrest which required bystander cardiopulmonary resuscitation from a colleague prior to commencement of lysis protocol at the local hospital. Transfer was later arranged to the nearest cardiac catheterization laboratory where a rescue percutaneous coronary intervention was performed in the left anterior descending artery that required strict dual antiplatelet use. Beneath the shroud of these events was a life-threatening right-sided hemothorax from rupture of intercostal arteries that occurred during initial resuscitation. Astute recognition of this post-percutaneous coronary intervention resulted in eventual transfer of the patient to a tertiary center where the source and the collection of the bleed was addressed. The patient’s took a great trajectory to improvement. Conclusions: A regional center poses many challenges and limitations. Massive bleeding from intercostal arteries leading to hemorrhagic shock and respiratory compromise from an expanding hemothorax post-CPR is rare. Post-percutaneous coronary intervention use of dual antiplatelets posed a management dilemma that prompted assistance from tertiary counterparts. Clinicians should be astute and quick in assessing and providing care.